Desain Lembar Kerja Peserta Didik Berbasis Predict Observe Explain Pada Pembelajaran Fisika Kelas X Semester I - Lelfita Lelfita; Nelfi Erlinda (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This research is motivated by the lack of attractive learning materials used by teachers, so that students have difficulties in understanding the lessons. One solution is to design learning materials in the form of Student Worksheets (LKPD) using a learning model that can improve the abilities and interests of students. The model used in the design of this LKPD is a model (Predict Observe Explain POE. The research carried out includes the type of Research and Development (R&D). The data collection instrument is an LKPD questionnaire based on the Predict Observe Explain model, a questionnaire to determine the practicality of the LKPD. LKPD based on the Predict Observe model Explain was tested at SMAN 2 Lubuk Alung Class X Semester 1. Based on the results of the LKPD validation analysis by the validator, a valid LKPD was obtained with an average score of 79.13% of the validity of the lecturer's questionnaire, and 80% of the validity of the teacher's questionnaire. POE-based LKPD which is very practical with an average score of 78.30% of the practicality of teachers, and 85.83% of practicality of students.